HUBUNGAN AKTIVITAS BELAJAR MANDIRI DENGAN HASIL BELAJAR RANGKAIAN LISTRIK - Cintya Trikirana; Soeprijanto; Farried Wadjdi (Fakultas Teknik Universitas Negeri Jakarta, 2017)
This research aims to knowing description data of individual learning activities and determine whether there is a positive and significant relationship between individual learning activities with learning outcomes of Electrical Circuit. This research was conducted at SMKN 26 Jakarta. The method used is survey method with correlational approach. Data collection of dependent variables using the test of learning outcomes. The population in this study were students of class X TIPTL which amounted to 60 students. The sampling technique using simple random sampling. The sample of this research are 51 students. The collected data will be processed by hypothesis test, correlation coefficient test and coefficient of determination test after the data fulfill the normal and linier requirements. The results showed that the average of individual learning activities is 94.35 it means individual learning activities of students of class X SMKN 26 Jakarta entered into enough category of individual learning activities, the detail frecquency of each individual learning activities category as follows: Students who entered very high category of individual learning activities is 19.60%. High category of individual learning activities is 25.49%. Low category of individual learning activities that is 15.69%. The most students included into enough category of individual learning activities is 35.29% and at least into very low category of individual learning activities is 3.92%. The result of this research is tcount > ttable (7.89 > 2.01) and correlation coefficient value 0.748, this result showed that there is positive and significant correlation between individual learning activities with learning outcomes of Electrical Circuit. Abstrak Penelitian ini bertujuan untuk mengetahui gambaran aktivitas belajar mandiri siswa dan mengetahui apakah terdapat hubungan yang positif dan signifikan antara aktivitas belajar mandiri dengan hasil belajar mata pelajaran Rangkaian Listrik. Penelitian ini dilakukan di SMK Negeri 26 Jakarta. Metode yang digunakan adalah metode survey. Pengumpulan data variabel terikat menggunakan tes hasil belajar dan pengumpulan data variabel bebas menggunakan kuesioner. Populasi dalam penelitian ini adalah siswa kelas X TIPTL yang berjumlah 60 siswa. Teknik pengambilan sampel menggunakan simple random sampling. Sampel penelitian berjumlah 51 siswa. Hasil penelitian menunjukkan bahwa nilai rata rata aktivitas belajar mandiri siswa yaitu 94,35 sehingga aktivitas belajar mandiri siswa kelas X SMK Negeri 26 Jakarta masuk ke dalam kategori aktivitas belajar mandiri cukup tinggi. Hasil penelitian menunjukkan bahwa nilai rata rata hasil belajar Rangkaian Listrik yaitu 83,94 sehingga hasil belajar Rangkaian Listrik masuk ke dalam kategori tinggi. Hasil penelitian diperoleh nilai thitung > ttabel (7,89 > 2,01) dan nilai koefisien korelasi sebesar 0,748, hasil ini menunjukan bahwa terdapat hubungan yang positif dan signifikan antara aktivitas belajar mandiri dengan hasil belajar Rangkaian Listrik.